Предмет: Математика,
автор: DaryaApart
11 БАЛЛОВ!
Упростить выражение:а) (9 - 5y+4) - (4 - 7) б) 5 *(3-)
Ответы
Автор ответа:
0
(9y^2 - 5y+4) - (4y^2 - 7 ) = 9y^2 - 5y + 4 - 4y^2 + 7 = 5y^2 - 5y + 11
==================
5x^2 * (3 - x^7) = 15x^2 - 5x^8
==================
5x^2 * (3 - x^7) = 15x^2 - 5x^8
Похожие вопросы
Предмет: Английский язык,
автор: saskacibulka48
Предмет: Алгебра,
автор: ctgfgygzgfcjy
Предмет: Алгебра,
автор: poosh90
Предмет: Математика,
автор: viktgolovina
Предмет: Химия,
автор: olenmazoxist